Kidney stones among Iranian adults: Prevalence and socioeconomic inequality assessment in a cohort‐based cross‐sectional study - Telma Zahirian Moghadam; Farhad Pourfarzi; Hamed Mohseni Rad; Hamed Zandian (Health Science Reports, 2022)
Abstract Background and Aims Kidney stone disease is a crystal concretion formed usually within the kidneys. The worldwide prevalence of kidney stones could be affected by numerous differences in socioeconomic, and environmental factors. The purpose of this study is to investigate kidney stones among Iranian adults aged between 35 and 70 years and the prevalence and evaluation of socioeconomic inequalities. Methods In this, a cohort‐based cross‐sectional study was carried out among 20,427 participants of ArNCDs aged 35 and 70 years old. Kidney stone was defined as a dependent (and binary) variable while demographic and socioeconomic factors were considered independent variables. Multivariable logistic regression was used to identify the key socioeconomic factors affecting kidney stone prevalence in Ardabil. Results The overall prevalence of kidney stones was 17.6 (95% confidence interval [CI]: 16.1–19.2) out of which 21.53% and 14.36% pertained to men and women and 14.18% and 23.17% pertained to the poorest and richest groups, respectively. There was a significant difference in the prevalence of kidney stones between men and women in terms of age, marital status, education level, chronic disease, body mass index, and socioeconomic status (<0.001). The prevalence of kidney stones had a positive correlation with age (1.7, 95% [CI]: 1.42–2.04) and socioeconomic status (1.5, 95% [CI]: 1.34–1.69), where the odds of kidney stones increased significantly by increasing age and socioeconomic status. Moreover, the kidney stone concentration index showed a pro‐rich distribution wherein it was more common among wealthy people (higher socioeconomic status) 0.062 (95% [CI]: 0.051–0.072). Conclusion The results of this study showed that there is significant inequality in the prevalence of kidney stones, where it was more common among the richest people. In addition, being men and old age are significantly related to kidney stones, so policymakers and physicians should consider these factors.